2006
DOI: 10.1124/jpet.106.113332
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and Neonatal Nicotine Exposure Differentially Regulates Vascular Contractility in Adult Male and Female Offspring

Abstract: Epidemiologic studies suggest that prenatal exposure to maternal cigarette smoking is associated with an increased risk of elevated blood pressure in postnatal life. The present study was designed to test the hypothesis that fetal and neonatal nicotine exposure increased vascular contractility in adult offspring. Nicotine was administered to pregnant rats via s.c. osmotic minipumps throughout gestation and up to 10 days after delivery. Aortas were isolated from adult male and female offspring at the age of 3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
68
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 42 publications
17
68
3
Order By: Relevance
“…14 In the developing fetal lung, nicotine inhibits maturation and disrupts alveolar number, structure, and function. 15 Prenatal exposure to nicotine has also been shown to increase contractile responsiveness of the aortae to norepinephrine and KCl 16,17 and increase the susceptibility to ischemia/reperfusion injury in male rat offspring.…”
Section: Introductionmentioning
confidence: 99%
“…14 In the developing fetal lung, nicotine inhibits maturation and disrupts alveolar number, structure, and function. 15 Prenatal exposure to nicotine has also been shown to increase contractile responsiveness of the aortae to norepinephrine and KCl 16,17 and increase the susceptibility to ischemia/reperfusion injury in male rat offspring.…”
Section: Introductionmentioning
confidence: 99%
“…5 Our recent studies in the rat have demonstrated that fetal nicotine exposure causes reprogramming of vascular reactivity and produces genderdependent alterations in both ␣ 1 -adrenoceptor-mediated contractions and endothelial NO synthase (eNOS) activity of arteries in adult offspring. 6 In addition, fetal nicotine exposure resulted in an in utero reprogramming of protein kinase C isozyme gene expression pattern in the developing heart and increased heart susceptibility to ischemia and reperfusion injury in adult offspring. 7 Angiotensin II (Ang II) plays a fundamental role in the regulation of cardiovascular homeostasis and has been implicated in the pathophysiology of hypertension induced by adverse in utero environment during the fetal development.…”
mentioning
confidence: 99%
“…Thus, fetal and neonatal nicotine exposure alters vascular functions in adult offspring in a gender-specific manner, which may lead to an increased risk of cardiovascular dysfunction in later life. 17 Furthermore, maternal smoking seems to promote stiffening of the fetal aorta during gestation. 18 Oxidant stress appears to play a major role in the inflammatory response to smoking.…”
mentioning
confidence: 99%